factorise by splitting the middle term:6x square-11x+5
Answers
Answered by
2
Step-by-step explanation:
=> 6x² - 11x + 5
=> 6x² - 6x - 5x + 5
=> 6x (x - 1) - 5(x - 1)
=> (x - 1) (6x - 5)
Answered by
2
Answer:
- plsss see the attachment
Attachments:
![](https://hi-static.z-dn.net/files/d79/10d7d247c43cc91f0c4435d7f22e879d.jpg)
Similar questions
English,
5 months ago
Math,
5 months ago
English,
5 months ago
Math,
11 months ago
World Languages,
11 months ago
Political Science,
1 year ago
Math,
1 year ago